(untitled) (Journal of Science and Technology, 2015)
An impressive scientific research infrastructure has been built up in Ghana over the years in recognition of the important role of science and technology In economic development. It is felt, however, that the institutions. engaged In research are not making significant Impact on the development of the country. Some of the problems responsible for this are discussed and some ways of improving the situation are suggested. It is argued that in the absence of an explicit policy statement on science and technology and a clear definition of their place in the country’s development plans the impact of the research effort is likely to remain limited. The discussion is brief and no attempt is made to cover all the complex issues involved. The object of the paper is merely to stimulate further discussion.